Time-independent schrodinger-poisson coupled simulation based study of InP and InAlAs quantum well field effect transistors - Ahsan, Mehdi; Hayat, Abrar; Nath, Apurba (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.